Konsep Waḥy dalam Kajian Semantik - Arif Nursihah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Waḥy an important term in Islam, has previously used by the Arabs before the advent of Islam. Waḥy, with various derivations, has a very strong character of meaning. It represents a form of communication related to two persons. The media can be either verbal or non-verbal, and it always has mysterious elements as well as some secrets. No matter how many lexical or derivation forms (isytiqāq) of this word, all of them are connected to the meaning of disclosure something quickly.[Waḥy sebuah istilah penting dalam agama Islam, sejatinya sudah digunakan orang-orang Arab sebelum kedatangan Islam. Waḥy dengan berbagai derivasinya, memiliki karakter makna yang sangat kuat. Ia merupakan bentuk komunikasi yang berhubungan dengan dua orang, medianya bisa berupa verbal ataupun non-verbal, dan kandungannya senantiasa mengandung unsur misteri dan rahasia. Betapapun banyak bentuk isytiqāq dari kata ini, akan tetapi kesemuanya terhubung dalam relasi makna pengungkapan sesuatu secara cepat.]